Physiological responses to heat stress in an invasive mussel Mytilus galloprovincialis depend on tidal habitat. (February 2020) - Collins, Christina L.; Burnett, Nicholas P.; Ramsey, Matthew J.; Wagner, Kaitlyn; Zippay, Mackenzie L.
Abstract: Mussels are ecologically important organisms that can survive in subtidal and intertidal zones where they experience thermal stress. We know little about how mussels from different tidal habitats respond to thermal stress. We used the mussel Mytilus galloprovincialis from separate subtidal and intertidal populations to test whether heart rate and indicators of potential aerobic (citrate synthase activity) and anaerobic (cytosolic malate dehydrogenase activity) metabolic capacity are affected by increased temperatures while exposed to air or submerged in water. Subtidal mussels were affected by warming when submerged in water (decreased heart rate) but showed no effect in air. In contrast, intertidal mussels were affected by exposure to air (increased anaerobic capacity) but not by warming. Overall, physiological responses of mussels to thermal stress were dependent on their tidal habitat. These results highlight the importance of considering the natural habitat of mussels when assessing their responses to environmental challenges. Highlights: We tested how warming and exposure to air affected mussels from two tidal habitats. Subtidal mussels decreased heart rate with warming, but only while submerged. Heart rate of intertidal mussels was unaffected by temperature and exposure to air. Aerobic and anaerobic enzymatic activity of all mussels were unaffected by temperature. Only intertidal mussels changed anaerobic capacity (increased) when exposed to air.